Velocity effects on slip evolution of faults subjected to constant and cyclic normal stress derived from laboratory tests - Kang Tao; Wengang Dang; Heinz Konietzky; Yu Liu; Wenhao Zhang; Xingling Li (Rock Mechanics Bulletin)
Understanding the slip-style evolution of tectonic faults is important for exploring the earthquake mechanisms. To reveal the fault slip characteristics under a complex stress state, we conducted a series of laboratory friction tests on saw-cut granite joint surfaces. The effects of load point velocity and normal stress disturbances were investigated. Based on laboratory observations, a one-dimensional Spring-Block model was developed to interpret the frictional behavior. Under constant normal stress, the simulated fault (granite joint) exhibits a regular stick-slip phenomenon at different load point velocities with stable recurrence intervals and stress drop magnitudes. Under cyclic normal stress, when the load point velocity is slow, stick-slip events occur only after 4–5 cycles of normal stress loading. When the load point velocity is large, due to the rapid sliding of the joint interface, one normal stress cycle can lead to 4–5 stick-slip events. We find that the cyclic normal stress weakens the joint shear strength when the load point velocity is slow and improves the strength when the velocity is fast. There is a critical value of load point velocity for resonance where the stick-slip occurrence timespan is identical to the normal stress cyclic period. This work sheds light on the frictional evolution of tectonic faults during the seismic cycles influenced by a complex stress state.